Population pharmacokinetic and pharmacodynamic modeling of different formulations of ONO‐5334, cathepsin K inhibitor, in Caucasian and Japanese postmenopausal females. (10th October 2013) - Hasegawa, Chihiro; Ohno, Tomoya; Umemura, Takeo; Honda, Naoki; Ohyama, Michiyo; Nagase, Shinichi; Small, Maria; Deacon, Steve; Ogawa, Mikio; Ieiri, Ichiro
Abstract ONO‐5334, a selective inhibitor of cathepsin K, is a potential new treatment for osteoporosis. The objectives of this study were to (1) develop population pharmacokinetic–pharmacodynamic (PK–PD) models for ONO‐5334 using dose‐ascending data from healthy postmenopausal females, (2) examine comparability of PK and/or PD profile between Caucasian and Japanese, and (3) compare PK–PD profile between immediate release tablet (IRT) and sustained release tablet (SRT). The population PK–PD models were developed for each formulation for post‐dose levels of bone resorption markers (serum CTX and NTX). The data were provided from 4 phase 1 studies with total of 201 Caucasian and 94 Japanese subjects. Plasma concentrations of ONO‐5334 and bone resorption markers were thoroughly evaluated in those studies. An indirect response model described relationships between bone resorption markers and plasma concentrations of ONO‐5334. There was no significant difference in PK and pharmacodynamic potency (IC50) between Caucasian and Japanese. Based on the developed model, serum CTX and NTX after administration of ONO‐5334 IRT or SRT were simulated, and the results showed that ONO‐5334 SRT would provide comparable PD effect on bone resorption markers with lower dose relative to IRT.